The Vikings - Thompson, Ben, 1980- (Thompson, Ben, 1980- Guts & glory., 2015)
From battle-axe-wielding tribes plundering the greatest cities of Europe to powerful kings and queens ruling their dominions with iron fists, the Vikings were some of the most feared and fearless figures in European history. Find the bravest heroes, the most menacing villains, and unbelievably awesome facts and myths inside this action-packed overview.